The impact of track and field sports professionalization on age limits of athletes sports skills qualifications saving. - Kozlova O.K (Kharkov National Pedagogical University, 2011)
The age-related features of elite athletes were defined track-and-field events. It was established, that professionalization of track-and-field sport assists the expansion of the age limits elite athletes performances on a world of sporting arena. The most of sportsmen age of which exceeds 30 years is specialized in such of track-and-field events: race walking 50 km (men) - 56,7 %; hammer throw (men) -46,7%; discuss throw(women) - 46,7%.